Pembinaan Akhlak Remaja Berbasis Kolaborasi Guru dan Orang Tua: Kajian Systematic Literature Review - Wildan Murtadho; Siti Halimah; Salminawati Salminawati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This research aims to analyze the efforts of teachers, parents, and forms of collaboration in developing adolescent morals. This type of research is part of qualitative research using the Systematic Literature Review (SLR) model by searching 161 articles through the DOAJ and Garuda databases, selecting 13 articles according to the criteria. The research results show the teacher's holistic efforts through strategies towards students and their key role in shaping the character of teenagers. Collaboration between parents and teachers involves various methods, includes internal and external aspects, and adapts to the local cultural and educational context. This review indicates that collaboration between teachers and parents has a crucial role in shaping the character and morals of adolescents, supporting the view that moral education for adolescents requires synergistic support and cooperation. This research also provides directions for future research, including technological, cultural, organizational and behavioral aspects at different levels and regions.